Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

(a + b)² = a² + 2ab + b2 with step by step explanation​

Sagot :

Step-by-step explanation:

Given: (a+b)²

To prove: (a+b)² = a² + 2ab + b²

Proof:-

(a+b)² = (a+b)(a+b)

(a+b)²=a(a+b)+b(a+b)

(a+b)² = a²+ab+ab+b²

(a+b)² = a²+2ab+b².